Synthesis of a finger-like MoS2@VS2 micro–nanocomposite with enhanced field emission performance. Issue 22 (20th May 2020) - Feng, Yu; Du, Erwei; Gong, Shijing; Yu, Ke; Chen, Xiaofan; Zhu, Ziqiang
Abstract : A MoS2 @VS2 micro–nanocomposite showed enhanced field emission properties benefiting from the synergy of the two materials. Abstract : A MoS2 @VS2 micro–nanocomposite was synthesized via a two-step hydrothermal method. The field emission properties of the MoS2 @VS2 micro–nanocomposite were investigated for the first time. The finger-like VS2 has a larger field-enhancement factor than the common sheet-like morphology. Besides, MoS2 composited with VS2 not only improves the stability, but also improves the field emission performance of the sample greatly. Compared with pure MoS2 and VS2, the MoS2 @VS2 composite sample has the best field emission performance, including low turn on (0.8 V μm −1 ) and threshold fields (1.6 V μm −1 ), small work function, large field-enhancement factor, and good current stability. We attribute the enhanced field emission performance to the synergy of the two materials. We believed that the MoS2 @VS2 micro–nanomaterial reported in this work might be one of the best candidates for flat panel display materials.